PERAN PROFESIONAL PUSTAKAWAN DALAM PENGELOLAAN PERPUSTAKAAN MASA PANDEMI CORONA VIRUS-19 - Nana Ramadhani; Armizawati Armizawati; Tri Yuliani; Oktri Permata Lani (Alfuad: Jurnal Sosial Keagamaan, 2020)
This research discusses the role of librarians in managing libraries during the corona virus pandemic. The corona epidemic is an epidemic of globalization that cripples all access to services, including library services. Library services are a central aspect that will support the dissemination of the latest information related to the corona virus while maintaining the health and safety of readers through new innovations in the role of librarians in open access libraries. This research is a library research or library research that utilizes all journal literature related to librarian pran in developing pandemic service through online services and maximizing the librarian's function and role as an information management center. The results showed that many libraries have closed due to the epidemic, but many libraries have also opened online services so that online and offline visitor data is not too significant. It seems that the government provides more innovative means to support the innovative thinking of librarians in order to create online services that are more optimal, safe, healthy and environmentally friendly.